Universities as Drivers of the Urban Economies in Asia : The Case of Vietnam - Ca, Tran Ngoc (World Bank, Washington, DC, 2012)
This study looks at the contribution of the university system in Vietnam to the socioeconomic development in general, and their relationship with firms, dynamic actors of the economy in particular. The study uses different methods of research, from reliance on secondary data to interviews with universities and survey of firms. Several case studies of the key universities in four regions have been undertaken: Hanoi in the north, Danang in the center, and Ho Chi Minh City and Cantho in the south of Vietnam. The findings show that the role of Vietnamese universities in research is much weaker than teaching, and that their contribution to the socioeconomic development of the country is limited to the production of an educated labor force rather than innovation. However, in selected universities, innovation did take place to a certain extent and brought benefits for both the universities and firms they served. This situation is explained by both the inherited university system in Vietnam and its shift in behavior in the context of economic renovation and globalization.